Treatment of complex periorbital venolymphatic malformation in a neonate with a combination therapy of sirolimus and prednisolone. Issue 4 (5th March 2015) - Kim, David; Benjamin, Latanya; Wysong, Ashley; Hovsepian, David; Teng, Joyce
Abstract Venolymphatic malformations (VLMs) are vascular anomalies consisting of both veins and lymph vessels. A 2‐week‐old newborn presented with large VLMs on the left forehead, temple, preauricular area, and orbit. Patient was at imminent risk for permanent vision loss due to a localized mass effect. Surgical excision or debulking was contraindicated due to its complexity and proximity to the left eye, and the patient failed to respond to the sildenafil treatment and sclerotherapy. Patient was subsequently started on oral sirolimus 0.8 mg/m2 twice daily in combination with prednisolone 2 mg/kg daily. The patient had an excellent therapeutic outcome for 7 months with complete preservation of vision before treatment was discontinued. However, 2 months after the medical treatments were discontinued, her VLM rebounded. She responded to the combination therapy again after a failed treatment with the mTOR inhibitor alone. This case demonstrates that the sirolimus and prednisolone combination therapy could be beneficial for treatment of complex VLM intractable to other treatments.